2017
DOI: 10.1002/app.45852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the electrolyte content on the electrical permittivity, thermal stability, and optical dispersion of poly(vinyl alcohol)–cesium copper oxide–lithium perchlorate nanocomposite solid‐polymer electrolytes

Abstract: Solid‐polymer electrolytes (SPEs) in the form of poly(vinyl alcohol) (PVA) doped with various amounts (5, 10, and 15 wt %) of lithium perchlorate trihydrate (LiClO4·3H2O) and 2 wt % cesium copper oxide (Cs2CuO2) nanoparticles were fabricated by a solvent intercalation method. The obtained nanocomposites were evaluated for their chemical structure and microstructural and morphological behaviors via Fourier transform infrared spectroscopy, X‐ray diffraction, and scanning electron microscopy methods, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 49 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Because the series capacitances ( C 1 + C 2 ) represent the whole charge distribution for both the LiCoO 2 cathode and the sulfide solid electrolyte, the parasitical capacitance can reflect the size of the “space-charge layer” at the interface of the LiCoO 2 cathode/sulfide solid electrolyte quantitatively . From Table , it can be found that the parasitical capacitances, which is namely the differences of series capacitances, at the interface of the LiCoO 2 cathode/sulfide electrolyte decrease with the doping amount of WS 2 and LiBr clearly . This result demonstrates that the “space-charge layer effect” has been suppressed by the dual-doping of WS 2 and LiBr.…”
Section: Results and Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Because the series capacitances ( C 1 + C 2 ) represent the whole charge distribution for both the LiCoO 2 cathode and the sulfide solid electrolyte, the parasitical capacitance can reflect the size of the “space-charge layer” at the interface of the LiCoO 2 cathode/sulfide solid electrolyte quantitatively . From Table , it can be found that the parasitical capacitances, which is namely the differences of series capacitances, at the interface of the LiCoO 2 cathode/sulfide electrolyte decrease with the doping amount of WS 2 and LiBr clearly . This result demonstrates that the “space-charge layer effect” has been suppressed by the dual-doping of WS 2 and LiBr.…”
Section: Results and Discussionmentioning
confidence: 86%
“…25 From Table 3, it can be found that the parasitical capacitances, which is namely the differences of series capacitances, at the interface of the LiCoO 2 cathode/sulfide electrolyte decrease with the doping amount of WS 2 and LiBr clearly. 31 This result demonstrates that the "space-charge layer effect" has been suppressed by the dual-doping of WS 2 and LiBr. Furthermore, the difference value of capacitance between LPSW10Br and LiCoO 2 is the lowest among these four samples, depicting that the interfacial resistance between the sulfide solid electrolyte and LiCoO 2 cathode is the lowest.…”
Section: Acs Applied Materials and Interfacesmentioning
confidence: 79%
“…The materials containing 10–50 wt% of SOE showed even higher permittivity, in particular at the lower range of frequencies: At frequencies below 40 Hz, the permittivity increases significantly and reaches values as high as 10 4 at 0.1 Hz. These values are in the same range like for PEG‐based solid polymer electrolytes, and, at the current state of knowledge, are attributed to charge accumulation at the electrode‐polymer interface, which partially blocks the charge transport . The high permittivity values of the networks containing SOE are indicative of conductivities higher than those of common polymeric insulators (for the conductivity measurements themselves, see hereinafter).…”
Section: Resultsmentioning
confidence: 62%
“…Since, the electric field change is fast, charge carriers will not be able to keep in line with the field. Hence polarisation of a material decreases at the interface, both ε′ and ε″ decreases [25].…”
Section: Temperature Dependent Conductivitymentioning
confidence: 99%